Interrogating the nature of local economy and communal conflict disruption: conceptual implications for sustainable food security in Ebonyi State - Nwangbo, Sunday Odo; Ukeje, Ikechukwu Ogeze; Njoku, Chukwunenye Clifford; Ololo, Kennedy (University of Nigeria Journal of Political Economy, 2023)
This paper examines Ebonyi State local economy and its Effium/Ezza-Effium communal conflict which has implications on food security of the state. The aim of the study is to explore Ebonyi State’s local economic activities often disrupted by communal conflicts which affect food production and local sustainable development. The study utilises primary (online interview and transcription of historical video documentary) and secondary data with content analysis in its descriptive form as well as thematic explication of key issues, leveraging on ex post facto research design which helped to unravel historical background issues of the communal conflict, necessary in diagnosing the causes, effects and the future of the conflict situation. The entire study was anchored on the theory of Marxism apt in explaining the dynamics, impetus and implication of societal conflicts. The findings revealed that the conflict caused major devastation on the economic activities of the local area. Particularly, agricultural activities were disrupted, households, employees, traders and farmers were displaced, insecurity and proliferation of arms heightened, and ultimately, food scarcity and hike in food price ensued in the state especially its capital and the surrounding communities of the conflict area that witnessed massive influx of victims. The paper recommends among others, engagement of local stakeholders and authorities in timely arrest of causes of conflict, and to adopt inclusive resolution strategies in its dealings. Finally, it solicits for funding and placement of displaced farmers, and creation of safe environment for agriculture cum local economic activities.